Gender Ideology in the Study of Islamic Legal Thought at Postgraduate UIN K.H. Abdurrahman Wahid Pekalongan - Ali Muhtarom; Ade Dedi Rohayana; Maghfur Ahmad; Kurnia Muhajarah; Nur Hamid (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
The formation of gender ideology can occur at various levels, and allows it to be socialized through social and institutional institutions at various levels. One of them is a university where students learn to research and study Islamic law. Higher education is one of the vital media to build a gender responsive culture. The focus in this study is to analyze gender ideology that influences students in researching and writing scientific papers, and how gender construction in Islamic legal thinking is in student work. Based on this study using a qualitative-phenomelologic approach and descriptive-analytic in nature, it was found out that, first, the gender ideology of students in conducting research and writing scientific papers is justice and gender awareness, secondly, the construction of Islamic legal thought in Postgraduates can be grouped according to two; 1) the orientation or direction of graduate student gender studies is more dominated by contextual or applied-empirical studies than textual or normative-legalistic studies. 2) the direction of analysis of gender studies is more defined as a study